Analysis of Assessment for K13 Curriculum and Merdeka Curriculum at Senior High School Polewali Mandar: Analisis Penilaian Kurikulum K13 dan Kurikulum Merdeka di SMA Negeri Polewali Mandar - Nasaruddin; Abdul Haris Sunubi; Zulfah (Universitas Muhammadiyah Palu, 2024)
K13 Curriculum (Kurikulum 2013) in Indonesia emphasizes a holistic approach to student assessment, integrating cognitive, affective, and psychomotor domains and Merdeka Curriculum introduces a comprehensive assessment approach aimed at improving learning quality and student outcomes. It emphasizes diagnostic, formative, and summative assessments throughout the learning process. The research aimed to describe the assessment for K13 Curriculum and the assessment for Merdeka Curriculum. This research used Qualitative research with study cases approach with source of data primer and secondary data with the informan of 4 English Teacher at Senior High School Polewali Mandar, technique of analysiss used data reduction, display data dan conclution. The result of this research were as follow: 1) The Assessment for K13 Curriculum emphasizes a holistic approach to student assessment encompassing cognitive, affective, and psychomotor domains which teachers utilize authentic assessment to evaluate students' academic knowledge, social-emotional development, and practical skills which focused on student centered learning and real-world application underscores to preparing students with the skills and competencies necessary at classroom activities. 2) The Assessment for Merdeka Curriculum emphasizing diagnostic, formative, and summative assessments which teachers implement assessments that not only measure cognitive achievements but also consider affective and psychomotor aspects of student learning while comprehensive approach aims to enhance the quality of learning experiences by providing continuous feedback, identifying learning gaps, and ensuring students' readiness to progress academically by fostering a supportive learning environment and encouraging student autonomy learning during classroom activities.